MANAJEMEN PERUBAHAN DALAM MERESPONS TANTANGAN DAN MEMAKSIMALKAN PELUANG DI ERA TRANSFORMASI DIGITAL - Rahman, Ghani Abdur; Cahyani, Elia; Teratai, Nona Ratu Syifa Putri; Nururrohmah, Tazkiyyah; Situmorang, Sangaviery Loucas; Haludin, Guntur (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The era of digital transformation brings significant changes to the way organizations operate, creating new opportunities and challenges in various sectors. This study aims to analyze the role of change management in responding to challenges and maximizing opportunities in the era of digital transformation. Through an in-depth literature study, this study found that effective change management plays a key role in overcoming internal resistance, facilitating technology adoption, and accelerating organizational transformation. The main challenges faced include resistance to change, budget constraints, technology readiness, and rigid organizational culture. Strategies that have been successfully implemented by organizations include visionary leadership, continuous innovation, and a focus on developing digital skills. The determining factors for the success of digital transformation include top management commitment, active involvement of all members of the organization, and a clear roadmap. The results of the study also show that resistance to change can be overcome by employee involvement in decision-making, transparent communication, and training programs that support adaptation. This study concludes that well-planned change management allows organizations not only to survive, but also to optimally utilize the opportunities that exist in the era of digital transformation